Pemberdayaan Pengajar Sebagai Bentuk Pencegahan dan Penanggulangan Bullying Pada Santri di TPQ Al-Hakim Kota Malang - Syechfiansyah, Rossie; An-Khofiyya, Nida; Fitri, Rihadatus Syahwana; Chalisah, Siti Nur; Abdilla, Mohammad Nurul Faiz; Adhitama, Felicia Dewati Elit; Sulistyorini, Anita; Laksana, Dian Puspitaningtyas (Universitas Negeri Malang, 2024)
Bullying is an act of violence that is carried out intentionally and occurs repeatedly from a stronger person to a weaker person. The impact of bullying on students is in the form of disruption of physical and mental health which has caused some students to stop reciting the Koran. Santri who often experience bullying actions with vulnerable elementary school age (7-12 years) are more than 20 people. Thus we hold empowerment for TPQ Al-Hakim teachers, where later the teachers can coordinate with the students and guardians of the students, so that the teachers have a big role in preventing and overcoming bullying. The purpose of this teacher empowerment activity is carried out as an effort to prevent and overcome bullying that occurs in the TPQ Al-Hakim environment. The method used is to interact directly through the interview method to the TPQ Al-Hakim teachers. The results of this activity provide knowledge for teachers which includes an in-depth understanding of preventing and overcoming bullying in the TPQ environment, and approaching families so that they can hold consultations related to bullying. After the implementation of the activity, bullying behaviors in the TPQ environment are very minimal, which is the result of the activity.